2017
DOI: 10.1097/nmd.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Can Religion Protect Against Suicide?

Abstract: The vast majority of the world's population is affiliated with a religious belief structure, and each of the major faith traditions (in its true form) is strongly opposed to suicide. Ample literature supports the protective effect of religious affiliation on suicide rates. Proposed mechanisms for this protective effect include enhanced social network and social integration, the degree of religious commitment, and the degree to which a particular religion disapproves of suicide. We review the sociological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Some religious patients may also feel guilty about their suicidal ideation (Norko et al., ), nullifying the protective effect of R&S in these patients. It has also been suggested that spiritual struggles can cause suicidal crisis (Currier, McDermott, McCormick, Churchwell, & Milkeris, ), however, from our experience, this was rarely mentioned as cause by patients, though we did not systematically explored this risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some religious patients may also feel guilty about their suicidal ideation (Norko et al., ), nullifying the protective effect of R&S in these patients. It has also been suggested that spiritual struggles can cause suicidal crisis (Currier, McDermott, McCormick, Churchwell, & Milkeris, ), however, from our experience, this was rarely mentioned as cause by patients, though we did not systematically explored this risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not assess if therapists systematically prompted for R&S and actively included R&S in treatment. Furthermore, match or mismatch of patents and therapists R&S may lead to transference/countertransference issues that can be positive or negative for the progress in treatment (Norko et al., ). However, we think that this alternative hypothesis is unlikely to completely explain our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations